Novel Thermophilic Bacterial Laccase for the Degradation of Aromatic Organic Pollutants - Sharma, Nabangshu; Leung, Ivanhoe K.H. (Frontiers in Chemistry, 2021)
We identified a putative laccase from the thermophilic bacterium Geobacillus yumthangensis. The putative laccase was produced recombinantly and its ability to catalyse the degradation of aromatic organic pollutants was investigated. The putative laccase exhibits broad pH and temperature stability, and, notably, it could catalyse the degradation of organic dyes as well as toxic pollutants including bisphenol A, guaiacol and phenol with a redox mediator. Our work further demonstrates the potential of using oxidative enzymes to break down toxic chemicals that possess major threats to human health and the environment.